Charting the Journey: A Phenomenological Study of Novice Nurses’ Early Career Transition into Clinical Practice - Morales, Abby Claire C.; Funtecha, Mary Luz C.; Organia, Elmer G.; Montero, Jona Phie D.; Alave, Richard Deo Rox R.; Reyes, Andrea Celestine C.; Gonio, Lillien A.; Cabradilla, Pinky; Serra Jr. , Carlos O.; Batisla-ong, Angelie V. (MALATA SAINS INDONESIA, 2026)
Introduction: The transition from nursing education to professional practice is a crucial period marked by significant personal and professional adjustments. Understanding this process offers insights into the challenges, adaptations, and growth experienced by novice nurses as they begin their careers in healthcare. Objective: This study aimed to explore and describe the lived experiences of novice nurses during their transition from academic training to clinical practice, and to identify key factors affecting their early professional development. Methods: A descriptive phenomenological approach was employed. Ten registered nurses with a Bachelor of Science in Nursing and at least one year of clinical experience were selected through purposive sampling. Data were gathered via face-to-face in-depth interviews using a semi-structured interview guide. Colaizzi’s method was used to analyze the data, identifying significant meanings and themes that capture the essence of participants’ experiences. Results: Six themes emerged: Clinical and Emotional Adaptation, Workload Management, Confidence in Decision-Making, Transition to Autonomy, Handling Initial Hospital Exposure, and Integration into the Workplace. These themes collectively depict a complex transition process characterized by emotional vulnerability, heavy workload, and the gradual development of confidence and independence. Participants’ experiences highlighted the interaction between individual coping strategies and workplace factors, emphasizing how mentorship, workload, and organizational culture influence early professional adjustment. Conclusion: The findings suggest that the shift from student to professional nurse is not only a personal developmental journey but is also influenced by systemic and organizational factors. In the Philippine context, resource limitations and inconsistent support systems intensify the difficulties of transition, requiring novice nurses to rely on self-regulation and relational support. Strengthening structured transition programs, managing workloads, and improving mentorship are vital to supporting novice nurses, enhancing patient safety, and increasing workforce retention.